Fungicidal and molluscicidal activity of helioxanthin in Taiwania flousiana Gaussen and spatiotemporal dynamic of its content - Jiaxin CHEN; Xiaoyang BI; Lijuan ZHOU; Jiguang HUANG (Huanan Nongye Daxue xuebao)
ObjectiveTo determine the inhibition effect of helioxanthin from Taiwania flousiana Gaussen on three important plant pathogenic fungi, including rice sheath blight disease pathogen Rhizoctonia solani Kühn, rice leaf brown spot disease pathogen Nigrospora oryzae (Berk. & Br.) Petch and banana wilt disease pathogen Fusarium oxysporum Schlecht, as well as Pomacea canaliculate (Lamarck), and investigate the growth time, part and regional differences of helioxanthin content. MethodThe inhibition effect of helioxanthin on pathogenic fungi was determined by the mycelial growth rate inhibition method. The antifeedant activity of helioxanthin on P. canaliculata was tested by the leaf disc dipping method. The maximum absorption wavelength, standard curve as well as the growth time, part and region changes of helioxanthin content were determined by HPLC. ResultThe helioxanthin had obvious inhibition effect on R. solani, N. oryzae and F. oxysporum, with the median inhibitory concentrations of 7.38, 5.97 and 28.13 mg·L−1, respectively. In addition, it had obvious antifeedant activity against the young P. canaliculata, and the median antifeedant concentrations at 24 and 48 h were 41.62 and 11.22 mg·L−1, respectively. The maximum absorption wavelength of helioxanthin was 266 nm. The content of helioxanthin in T. flousiana was low from January to March, increased from April to May, and decreased from June to December, showing a regular annual growth cycle change. It was mainly distributed in root and bark, with the highest contents of 1459.33 and 1117.78 mg·kg−1, respectively. There were significant differences in the helioxanthin contents of T. flousiana five different parts between different tree ages in the same area. In addition, the contents of helioxanthin in T. flousiana from Ya’an, Sichuan Province was higher than that from Xingdoushan National Nature Reserve, Enshi, Hubei Province. The rehizosphere soil and rotten leaf soil of T. flousiana also contained helioxanthin. ConclusionThe inhibitory effects of helioxanthin on the three plant pathogenic fungi and P. canaliculata are obvious. The highest contents of helioxanthin are found in root and bark of T. flousiana and the content of helioxanthin varies among different growth durations, seasons, parts and regions.